2005
DOI: 10.1093/brief-treatment/mhi017
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Elder Abuse in Sweden: Voices of Older Persons

Abstract: The aim of this study was to explore the perceptions of elder abuse held by older persons in Sweden. Six focus group interviews were conducted. Through qualitative content analysis, the text revealed four themes: causes of elder abuse, conceptions of elder abuse, consequences of elder abuse, and coping with elder abuse. Changing society and families, as well as individual determinants, were believed to be causes of elder abuse. The main conception of elder abuse was that of robbery or assault, and the main con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 38 publications
4
36
1
1
Order By: Relevance
“…Becoming fearful was the most important consequence of elder abuse reported in the some of the literature (Erlingsson, Saveman, & Berg, 2005). Our findings documented that abuse in older adults also results in emotional distress, loss of self-confidence and low self-esteem, depression, social isolation and increased health problems McAlpine 2008;Zink et al, 2006).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Becoming fearful was the most important consequence of elder abuse reported in the some of the literature (Erlingsson, Saveman, & Berg, 2005). Our findings documented that abuse in older adults also results in emotional distress, loss of self-confidence and low self-esteem, depression, social isolation and increased health problems McAlpine 2008;Zink et al, 2006).…”
Section: Discussionsupporting
confidence: 66%
“…The need to give a meaning to the abuse was a constant preoccupation of the elders. In this study explanations of abuser's actions were often lifted from the individual level to the societal level as in other studies findings (Erlingsson, Saveman, & Berg, 2005). Many elders did not find an explanation for what happened to them, especially when their own children become perpetrators, maybe due to the emotional conflict that they had to face (love and hate, care and fear).…”
Section: Discussionmentioning
confidence: 47%
“…Interviews with six groups of community-dwelling older persons over 63 years (n = 37) in Sweden (Erlingsson, Saveman, & Berg, 2005) identified changes in society and particularly social decline and poor government as primary causes of abuse. These older people felt that insufficient emphasis was given to funding and training health and care staff, and schools did not instill in children appropriate respect for older people.…”
Section: Societymentioning
confidence: 99%
“…Typologies of abuse and perceptions of severity or prevalence are most frequently described (Daskalopoulos, Mulin, Donovan, & Suzuki, 2006;Erlingsson, Saveman, & Berg, 2005;Hussein, Manthorpe, & Penhale, 2007;Lafferty, 2009). Hudson et al (1999) reported that over 90% of respondents aged between 45 and 93 years had heard the term elder abuse; this is similar to the level of awareness found in the present study.…”
Section: Previous Researchmentioning
confidence: 99%